2013
DOI: 10.3899/jrheum.130406
|View full text |Cite
|
Sign up to set email alerts
|

One Year After Mild Injury: Comparison of Health Status and Quality of Life Between Patients with Whiplash Versus Other Injuries

Abstract: Sociodemographic factors, preaccident psychological history prior to the accident, and PTSD were the main factors influencing QOL, rather than whether the injury was whiplash. PTSD may also be related to pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 41 publications
3
45
2
Order By: Relevance
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…To the best of our knowledge, we did not find any paper which included a comparable study population to evaluate HRQOL. Considering only patients with mild trauma, Hours et al [18] recently compared health status, effect on family, occupational consequences, and quality of life (HRQOL) 1 year after an accident between patients with whiplash vs. other mild injuries, and explored the relationship between initial injury (whiplash vs. other) and QOL. Socio-demographic factors, psychological history prior to the accident, and post-trauma stress disorder were the main factors influencing QOL, rather than the mechanism of injury.…”
Section: Quality Of Life In the Critically Illmentioning
confidence: 99%
“…Most reported transport accidents result in minor injuries (75%), mostly musculoskeletal and/or soft tissue injuries . The injury itself, regardless of severity, may lead to permanent mental and physical impairments and disabilities . Even though minor injuries comprise approximately 75% of all road transport injuries, poor physical and mental health outcomes in this group have received little attention .…”
Section: Introductionmentioning
confidence: 99%